Prevalence of Lower Urinary Tract Symptoms and Affecting Factors in Female University Students in Türkiye - Dinç, Ayten (Urology Journal, 2023)
Purpose: Lower urinary tract symptoms (LUTS) are common in women, and negatively affect their lives. The aim of this study is to determine the frequency of LUTS and its affecting factors in female graduate students in Turkey. Materials and Methods: This descriptive, cross-sectional study consisted of 815 women attending education at Canakkale Onsekiz Mart University. Data were; provided sociodemographic characteristics, a questionnaire, and the Bristol Female LUTS Scale. Linear regression analysis was used to identify the risk factors associated with LUTS. Results: According to the data obtained, the prevalence of at least one of the LUTS was determined as 71.8% (515/815). It was determined that the prevalence of storage symptoms was higher than that of voiding and urinary incontinence. According to the results of the linear regression analysis, the risk factors for LUTS in female student were hold urine at school, complaints of urinary incontinence in family, bedwetting in children, constipation, regular drug use, obesity. Conclusion: Consequently, LUTS is a common condition in female students. It is recommended to organize well-attended and repeated training programs for university students on healthy living behaviors, urinary habits, and hygiene.